The lost tomb : and other real-life stories of bones, burials, and murder - Preston, Douglas J. (GCP, 2023)
"What's it like to be the first to enter an Egyptian burial chamber that's been sealed for thousands of years? What horrifying secret was found among the prehistoric ruins of the American Southwest? Who really was the infamous the Monster of Florence? Douglas Preston's journalistic explorations have taken him from the haunted country of Italy to the jungles of Honduras. He was granted exclusive journalistic access to the largest tomb in Egypt's Valley of the Kings, broke the story of an extraordinary mass grave of animals killed by the asteroid impact that ended the Cretaceous period and caused the extinction of the dinosaurs, and explored what lay hidden in the booby-trapped Money Pit on Oak Island. When he hasn't been co-authoring bestselling thrillers featuring FBI Agent Pendergast, Preston has been writing about some of the world's strangest and most dramatic mysteries. The Lost Tomb brings together an astonishing and compelling collection of true stories about buried treasure, enigmatic murders, lost tombs, bizarre crimes, and other fascinating tales of the past and present"--